2008
DOI: 10.1002/masy.200850202
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Ionic Liquids with Polysaccharides – 2: Cellulose

Abstract: Some general comments about ionic liquids (ILs) and carbohydrates are given. The main scope of the review is to discuss the present state of the art of chemical modification of cellulose applying IL as reaction media considering own research results. ILs, namely 1‐butyl‐3‐methylimidazolium chloride (BMIMCl), 1‐ethyl‐ 3‐methylimidazolium chloride (EMIMCl), 1‐butyl‐2,3‐dimethylimidazolium chloride (BDMIMCl), 1‐allyl‐2,3‐dimethylimidazolium bromide (ADMIMBr) and 1‐ethyl‐3‐ methylimidazolium acetate (EMIMAc) are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
77
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(81 citation statements)
references
References 35 publications
2
77
0
2
Order By: Relevance
“…For instance, the ability to dissolve cellulose is often dependent on the basicity of the IL (Fukaya et al 2006(Fukaya et al , 2008King et al 2012;Parviainen et al 2013), but there are exceptions, e.g., tetraalkylphosphonium salts Holding et al 2014), which are basic but require a dipolar aprotic co-solvent to dissolve cellulose. In previous literature, the use of imidazolium based ILs, with alkyl substituents (ethyl, methyl, and allyl) and chloride, bromide or acetate anions, typifies most publications on cellulose dissolving ILs (Heinze et al 2008;Swatloski et al 2002). In regard to developing commercial processes, the potential environmental impacts of ILs are also of concern.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the ability to dissolve cellulose is often dependent on the basicity of the IL (Fukaya et al 2006(Fukaya et al , 2008King et al 2012;Parviainen et al 2013), but there are exceptions, e.g., tetraalkylphosphonium salts Holding et al 2014), which are basic but require a dipolar aprotic co-solvent to dissolve cellulose. In previous literature, the use of imidazolium based ILs, with alkyl substituents (ethyl, methyl, and allyl) and chloride, bromide or acetate anions, typifies most publications on cellulose dissolving ILs (Heinze et al 2008;Swatloski et al 2002). In regard to developing commercial processes, the potential environmental impacts of ILs are also of concern.…”
Section: Introductionmentioning
confidence: 99%
“…The ILs that are able to dissolve cellulose include several classes of cations and a multitude of anions. Some of the most common cations are imidazolium, pyridinium, ammonium, and phosphonium derivatives [16]. Although imidazolium-based ILs are known to form covalent bonds with cellulose in some cases [17,18], they are still among the most used in academic research on ILs and cellulose and still highly interesting for biomass processing [19].…”
Section: Introductionmentioning
confidence: 99%
“…The co-solvent MIM is known to catalyze some reactions. For the trimethylsilylation of cellulose in imidazolium based ionic liquids, it was found that the amount of MIM, which is a starting molecule for the synthesis of the solvent, had an impact on the degree of substitution in the final product (Kohler et al 2008). Furthermore, in DMAc/LiCl, the esterification of cellulose by carboxylic acid anhydrides is efficiently catalyzed by imidazole (Nawaz et al 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Second, in the specific case of using [EMIm][OAc] as a solvent, the addition of large amounts of a co-solvent reduces the amount of acetate ions available for cellulose acetylation as the side reaction. Third, in some cases, secondary solvents are actually required for a successful reaction to take place at all (Kohler et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation